The Distribution of Warfarin (Coumadin) in the Rat - Anderson, G. F (Thrombosis and Haemostasis, 1967)
It has been demonstrated that Coumadin, warfarin sodium, following intravenous administration in male albino rats was distributed quickly throughout the plasma and that the liver tissue has an affinity for the uptake of Coumadin as early as 1 hr. Other soft tissue organs demonstrated some early uptake but the activity was minimal by 24 hrs while the liver still possessed about two times the activity of other tissues studied.